P-graph approach for GDP-optimal allocation of resources, commodities and capital in economic systems under climate change-induced crisis conditions. (1st April 2015) - Aviso, K.B.; Cayamanda, C.D.; Solis, F.D.B.; Danga, A.M.R.; Promentilla, M.A.B.; Yu, K.D.S.; Santos, J.R.; Tan, R.R.
Abstract: Climate change impacts may manifest via multiple pathways, often leading to a shortage of resources, reduction in production capacities, or reduction in available labor inputs that are vital for economic activities. Effective climate change adaptation strategies are needed to determine the optimal allocation of scarce resources, commodities or capital under crisis conditions to minimize the economic consequences. In such cases, it is necessary to account for structural properties of economic systems to ensure that rational distribution policies are implemented. Input–output models are used to illustrate interdependencies among economic sectors and to assess both direct and indirect effects of disruptive events. Alternatively, these interdependencies may be exploited for developing effective recovery efforts to minimize the ripple effects of a crisis. In this paper, a process graph representation of the input–output model is developed to generate a rational procedure for the allocation of scarce resources, commodities or capital during crisis conditions. The process graph model is a graph-theoretic approach originally developed for chemical process design applications. The analogous problem structure allows it to be used for the input–output system. The method is demonstrated through several case studies to identify allocation policies geared towards reducing the impact of disruptions attributed to critical resources, commodities, or capital. Results show that depending on the economic structure, the optimal allocation of scarce resources, commodities or capital will satisfy the final demands of some economic sectors and reduce the production capacity of others in order to minimize the reduction of total gross domestic product. Though similar results can be obtained through traditional mathematical programming models, the process graph platform has the advantage to visually present the distribution of scarce resources, commodities or capital within the system. This work is a first attempt to implement the process graph approach in the fields of economics and climate change adaptation. In conclusion, the process graph based approach developed in this work can be used to provide policymakers with insights in developing appropriate risk mitigation plans associated with climate change-induced crisis conditions. Potential applications include both the development of disaster preparedness measures for anticipated disruptions, as well as the implementation of real-time emergency response in the midst of a crisis. Graphical abstract: Highlights: Process graph approach is proposed for optimal allocation in economic systems. Allocation gives minimum gross domestic product loss during climate-induced crises. Three case studies illustrate the proposed approach for realistic scenarios.